(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2016)
The aim of this study was to investigate the impact of teaching activities supported by Google SketchUp, which is a 3–Dimensional modeling software, and concrete models on the basic skills related to spatial ability in teaching geometric solids. The study sample consisted of 72 preservice teachers who were studying elementary mathematics education in 2009-2010 academic–year in a state-funded university in Central Anatolia, Turkey. This was an experimental study. The study used a pretest posttest control group design and included two experimental groups and a control group. One of the experimental groups was taught using Google SketchUp while the other one was taught with concrete model-aided teaching activities. The activities, designed for the control group, were carried out with some traditional teaching tools such as paper, pencil and classroom writing board. The Santa Barbara Solids Test (SBST) and the Purdue Spatial Visualization Test (PSVT) were used to measure spatial ability. The SBST measures the ability to mentally visualize the cross-sections of 3D objects. The PSVT consists of three parts: “Developments”, which measures skills to visualize a 3D object based on its surface development; “Rotations”, which measures skills to mentally rotate 3D objects; and “Views”, which measures skills to visualize different views of 3D objects. The study identified significant increases in the scores received for all of the tests by the group using Google SketchUp, in the scores received for the SBST and Developments part by the group using concrete models, and in the scores received for only the Developments part by the control group. Also, the posttest average score received for the “Views” part by the experimental group using Google SketchUp was significantly higher than the score of the experimental group using concrete models and the control group.